DAPT Attenuates Cadmium-Induced Toxicity in Mice by Inhibiting Inflammation and the Notch/HES-1 Signaling Axis - Yang, Jia-Ying; Shen, Dan-Yang; Wang, Jun; Dai, Jing-Feng; Qin, Xiao-Yan; Hu, Yang; Lan, Rongfeng (Frontiers in Pharmacology, 2022)
The small molecule DAPT inhibits the Notch signaling pathway by blocking γ-secretase mediated Notch cleavage. Given the critical role of the Notch signaling axis in inflammation, we asked whether DAPT could block Notch-mediated inflammation and thus exert neuronal protection. We established a mouse model of chronic exposure to cadmium (Cd)-induced toxicity and treated it with DAPT. DAPT was effective in ameliorating Cd-induced multi-organ damage and cognitive impairment in mice, as DAPT restored abnormal performance in the Y-maze, forced swimming and Morris water maze (MWM) tests. DAPT also reversed Cd-induced neuronal loss and glial cell activation to normal as observed by immunofluorescence and immunohistochemistry of brain tissue sections. In addition, Cd-intoxicated mice showed significantly increased levels of Notch/HES-1 signaling axis and NF-κB, as well as decreased levels of the inflammatory inhibitors C/EBPβ and COP1. However, DAPT down regulated the elevated Notch/HES-1 signaling axis to normal, eliminating inflammation and thus protecting the nervous system. Thus, DAPT effectively eliminated the neurotoxicity of Cd, and blocking γ-secretase as well as Notch signaling axis may be a potential target for the development of neuronal protective drugs.